2019
DOI: 10.1177/1474515119831511
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a nurse-led lipid-lowering secondary prevention intervention in patients hospitalized for ischemic heart disease: A pilot randomized controlled trial

Abstract: Background Lack of achievement of secondary prevention objectives in patients with ischemic heart disease (IHD) remains an unmet need in this patient population. Aims We aimed at evaluating the 6-month efficacy of an intensive lipid-lowering intervention, coordinated by nurses and implemented after hospital discharge, in patients hospitalized for an IHD event. Methods Pilot randomized controlled trial enrolling 78 patients (39 in each arm). A nurse-led intervention including follow-up, serial lipid level contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Recent surveys indicated that there is considerable potential for further improvements in the secondary prevention of CAD in European countries [11][12][13]. Many intervention methods aimed at improving secondary prevention in CAD patients have been proposed previously [14][15][16][17][18][19]. Additionally, several factors influencing the quality of secondary prevention in every-day practice have been identified [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Recent surveys indicated that there is considerable potential for further improvements in the secondary prevention of CAD in European countries [11][12][13]. Many intervention methods aimed at improving secondary prevention in CAD patients have been proposed previously [14][15][16][17][18][19]. Additionally, several factors influencing the quality of secondary prevention in every-day practice have been identified [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…High-risk ACS patients on this new pathway with LDL-C>190 mg/dL or statin intolerance, patients with LDL-C>100 mg/dL if already established on statin therapy, Lp(a) > 150 nmol/L, age<45 years were discharged on high dose statins and ezetimibe and were followed up in outpatient rehab clinic within two months [ 13 ]. The Euroaspire V study approach was different as patients in this pathway were followed by cardiologists and general practitioners [ 14 ]. They initiated this pathway to ensure that patients commenced lipid-lowering therapy during hospital admissions and had virtual cardiology clinic follow-ups in six weeks’ time.…”
Section: Reviewmentioning
confidence: 99%
“…These patients were referred to the hospital lipid clinic if LDL-C remained > 70 mg/dL for consideration of PCSK9 inhibitors. This significantly improved lipid control in patients and the percentage of patients achieving LDL-C < 70 mg/dL reached 64% in 2018 vs 30% in 2015 [ 3 , 13 , 14 ].…”
Section: Reviewmentioning
confidence: 99%
“…Considering the disappointing results in secondary prevention, we conducted a randomized pilot study to evaluate whether an intensive mHealth lipid-lowering intervention implemented after a hospitalization due to IHD was associated with a lower LDLc level. We demonstrated that this strategy was associated with improved management of LDLc levels compared with standard care alone ( 11 ). Our current study aimed to assess whether this same structured mHealth-based protocol helped improve LDLc levels after a hospitalization due to IHD in a real-life population.…”
Section: Introductionmentioning
confidence: 98%